UWI licenced to grow marijuana for research (2015)
Reports on the newly signed MOU between the UWI and the Ganja Growers and Producers Association of Jamaica to enable the University to engage independent contractors or other approved bodies in the groowing of Cannabis plants. Notes that UWI (Mona) Cannabis Research Institute will focus on identifying the different strains of marijuana, how the different strains interact with the human body as well as products that may be derived from the plant.
Keywords: CANNABIS